Total cost of ownership in shipping: A framework for sustainability - Peter J. Stavroulakis; Stratos Papadimitriou (Journal of Shipping and Trade (JST), 2022)
Shipping is pivotal for global commerce, yet its externalities are not yet fully set into context, especially with reference to environmental impact. Shipping is a practise developed from the dawn of history. Its manifestation requires the introduction of relevant supporting industries as well, such as port, cargo, and logistics operations. The holistic shipping system has been growing with its main parameter pertaining to accounting cost minimisation. Yet, the shipping ecosystem has been able to exacerbate environmental, social, and health costs that in the end may prove that shipping, in the way that it is conducted, may not be as profitable as it may seem.
Keywords: 650; Environment; Health cost; Shipping cost; Social cost; Total cost